Arthroscopically-assisted Latarjet: an easy and reproducible technique for improving the accuracy of graft and screw placement. Issue 2 (April 2018) - Taverna, Ettore; Guarrella, Vincenzo; Cartolari, Roberto; Ufenast, Henri; Broffoni, Laura; Barea, Christophe; Garavaglia, Guido
Background: The effectiveness of the Latarjet largely depends on accurate graft placement, as well as on proper position and direction of the screws. We present our technique for an arthroscopically-assisted Latarjet comparing radiological results with the open technique. Methods: We retrospectively reviewed the postoperative computed tomography scans of 38 patients who underwent a Latarjet procedure. For 16 patients, the procedure was performed with the open technique and, for 22 patients, it was performed using an arthroscopically-assisted technique. An independent radiologist evaluated graft and hardware position, as well as graft integration or resorption. Postoperative complications were also documented. Results: The graft was correctly placed in only 18.8% of cases in the open group and 72.7% of cases in the arthroscopically-assisted group. There were no postoperative complications in the arthroscopically-assisted group, whereas one patient had a recurrence and two required hardware removal in the open group. Conclusions: The Latarjet procedure is a challenging procedure for which a key point is the correct placement of the coracoid graft onto the glenoid neck and correct position of the screws. The present study substantiates a clear benefit for the use of a guide with an arthroscopically-assisted technique in terms of graft and hardware placement. At short-term follow-up, there appears to be a benefit for graft integration and avoidance of resorption.